2002
DOI: 10.1007/s00216-002-1470-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of eluent mixing on TLS detection in gradient elution HPLC

Abstract: The effects of changing solvent composition on the LOD of TLS detection in gradient elution HPLC have been studied from the perspective of thermo-optical properties of the solvent. Hyphenated gradient high-performance liquid chromatography (HPLC)-thermal lens spectrometry (TLS), was used to separate and detect 13 carotenoid compounds and two chlorophylls. Utilization of mixing coils into the system reduces the inhomogeneities during eluent changes and therefore enables the application of thermal lens detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Use of Cookson reaction products of 25(OH)D were not a feasible option to improve signal strength either since pre-column derivatization of the vitamin D compounds would affect and alter all carotenoids while post-column derivatization was not possible due to the reagent being fluorescent [63,64]. TLSD using laser light at 476 nm was found to result in up to 100-fold lower detection limits for carotenoids vs. absorbance monitoring at 450 nm in conventional HPLC systems [65] but this was reduced to 2–10 fold better detection limits with gradient elution [66]. TLSD is currently very difficult to implement owing to its commercial unavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Use of Cookson reaction products of 25(OH)D were not a feasible option to improve signal strength either since pre-column derivatization of the vitamin D compounds would affect and alter all carotenoids while post-column derivatization was not possible due to the reagent being fluorescent [63,64]. TLSD using laser light at 476 nm was found to result in up to 100-fold lower detection limits for carotenoids vs. absorbance monitoring at 450 nm in conventional HPLC systems [65] but this was reduced to 2–10 fold better detection limits with gradient elution [66]. TLSD is currently very difficult to implement owing to its commercial unavailability.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the authors have demonstrated the viability of on-line detection for supercritical fluid extraction with a pulse thermal lens spectrometer. Logar et al 6 have investigated the possibilities of improving the performance of TLS detection and to analyze the changes of thermo-optical parameters during the gradient elution HPLC. The authors have selected pigments (13 carotenoids and two chlorophylls) as model compounds, LODs for gradient separation with TLS detection are 1.3-to 10-fold lower than for the UV-Vis detection.…”
Section: Determination Of Carotenoidsmentioning
confidence: 99%
“…However, despite these problems thermal lens spectrometry has consolidated its positions, proving its viability. The method is more sensitive that conventional transmission spectrometry 6 because the photothermal effect amplifies the measured optical signal (relative change in the beam intensity). The enhancement depends on the thermal and optical properties of the sample and the properties of the pump and probe laser beam.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the very low concentrations of mercury (Hg) in natural waters (0.05-5.00 ng L -1 ), important loss and contamination problems can arise in sampling, sampling treatment and analysis processes [1][2][3][4][5][6][7]. The main mercury loss is due to Hg adsorption on bottle walls, but it is now recognized that the addition of acid (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…HCl) or oxidant (e.g. BrCl) allowed stabilisation of water samples for total dissolved Hg determination after filtration [4][5][6][7]. About contaminations, the routes are numerous and can lead to obtain erroneously high total mercury (Hg T ) concentrations [8].…”
Section: Introductionmentioning
confidence: 99%